Synthesis of isatin semicarbazones as novel anticonvulsants - Role of hydrogen bonding - Pandeya S.N.; Raja A.S.; Stables J.P. (My University, 2025)
Purpose: A series of substituted isatin semicarbazones and related bioisosteric hydrazones were designed and synthesised to meet the structural requirements essential for anticonvulsant properties. Methods: The structures of all synthesised compounds were confirmed by means of infrared, proton magnetic resonance spectroscopy and by elemental analyses. All compounds were evaluated for their anticonvulsant activity by maximal electroshock (MES), subcutaneous metrazol (ScMet) and subcutaneous strychnine (ScSty) induced seizure methods and their neurotoxic effects were determined by rotorod test. Results: A number of isatin semicarbazones exhibited significant protection after intraperitoneal administration at the dose of 100 and 300mg/kg. Some of them showed good anticonvulsant activity in MES test in rats after per oral administration at the dose of 30mg/kg. The bioisosteric hydrazone derivatives were inactive in all tests. Compound 6-chloroisatin-3- (4-bromophenyl)-semicarbazone has emerged as the most active analogue of the series showing good activity in all the three tests and was more active than phenytoin and valproic acid. Conclusions: The results evidenced the importance of hydrogen bonding and suggested a new pharmacophore model with four binding sites essential for anticonvulsant activity.